Modeling Risk-Based Stock Portfolio: Evidence from Long Time Series - Cahyadin, Malik; Riesendra, Luthfi Aradhana; Sarmidi, Tamat (EQUITY, 2025)
The judicious selection of a stock portfolio necessitates a meticulous and precise analysis of risk and return levels. Therefore, this study employs a simulation model to generate a practical and optimally diversified stock portfolio by considering risk level. Secondary data were employed on 952 Indonesian stocks and 4 global ETFs across four stages cover historical data, liquidity, risk-return performance, and fundamental indicators during 1st March 2007– 1st March 2025. Sharpe Ratio Maximization (SR Max) and Risk Parity (RP) methods were utilized. The findings reveal that during all daily data SR Max exhibited a Compound Annual Growth Rate (CAGR) of 16.15%, a volatility of 17.39%, and a drawdown of -39.11%. Meanwhile, RP recorded CAGR of 12.81%, a volatility of 13.24%, and a drawdown of -32.98%. By considering risk analysis, SR Max is appropriate for investors who accept high levels of risk in pursuit of significant growth opportunities. Conversely, RP is better suited to investors who prioritise stability and are willing to accept lower returns. Furthermore, the implication stimulates investors able to formulate a more rational and sustainable asset allocation strategies. In addition, the financial authority should pay more attention on the financial market stability. Keywords: Stock Portfolio; Risk Parity; Sharpe Ratio; Investor Decision Making.